Anatomical and Histological Study of Shark (Carcharhinus sorrah) Kidney - Hikmah Supriyati; Rakhmiyati Rakhmiyati; Muhammad Ja’far Luthfi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2019)
Sharks are sea water fishes belong to the class Chondrichthyes, Subclass Elasmobranchii. Sharks are cartilaginous fish that have a different osmoregulation process than any other sea water fish. Cartilaginous fish is the only vertebrate that can maintain urea. This study aims to determine the anatomical and histological structure of the kidney in the anterior, medial and posterior parts of kidney. The study was conducted by observing anatomy of the kidney. Histological preparations were made using the paraffin method. Qualitative descriptive data analysis was done. Research results show that shark kidneys consist of three parts, namely the head kidney, the body kidney, and the tail kidney. Kidney sharks are brownish red with a size of 18 cm long. Histological observations of shark kidney in the head kidney reveals many glomerulus, body kidney reveals many distal and tubule proximal contractile tubules whereas tail kidney reveals stroma that is rarely found in vertebrate kidney.